Eksekusi Mati Javanese Al-Hallaj Dalam Suluk Jawa - Muzairi Muzairi (UIN Sunan Kalijaga Yogyakarta, 2018)
It is very striking how Javanese Al Hallaj in the text of Suluk Jawa here published, is described as a mystic who propagated the “Science of Reality” to the uninitiated public imitating the conduct of Shaikh Siti Jenar, Sunan Panggung, Ki Bebeluk and Shaikh Amongraga. It is my intention here to discuss this common motif of conflict between traditional Javanese mysticism and orthodox, legalistic Islam, as reflected in these traditions, in order to gain some insight into the motif and significance of the Suluk Jawa.